Transition‐Metal‐Free [4+1] Cycloaddition for the Synthesis of 1, 2, 3‐Triazole from α, α‐Difluoro‐N‐Tosylhydrazone and Amine through C‐F Bond Cleavage. Issue 5 (17th October 2018) - Zhou, Qi; Fu, Zihao; Yu, Lefei; Wang, Jianbo
Abstract: An efficient synthesis of 1, 4‐disubstituted and 1, 4, 5‐trisubstituted 1, 2, 3‐triazole from α, α‐difluoro‐ N ‐tosylhydrazone and amine through a C−F bond cleavage protocol has been developed. α, α‐Difluoro‐ N ‐tosylhydrazone is used as a new reagent, which can transform amines to 1, 2, 3‐triazoles with high efficiency and excellent functional group compatibility without using transition‐metal catalysts, azide reagents and oxidants. Abstract : Base catalysed : An efficient transition‐metal‐free synthesis of 1, 4‐disubstituted and 1, 4, 5‐trisubstituted 1, 2, 3‐triazoles from α, α‐difluoro‐ N ‐tosylhydrazones and amines through a C−F bond cleavage has been reported.